AWARENESS ABOUT DIABETES AMONG ADOLESCENTS OF MANGALORE, SOUTH INDIA - Holla, Rohith; Prabhu, Sachin; Shetty, Sanjana; Deshpande, Shreya; K., Shwetha Balla; Hegde, Snigdha; S., Soujanya B.; Raj, Harsha; Kundapur, Rashmi (Journal of Health and Allied Sciences NU, 2014)
Introduction: India continues to be the diabetic capital of the world. According to the WHO report, India today heads the world with 32 million patients and this number is projected to increase to 79.4 million by the year 2030. Diabetes has become a great economic challenge as it drains between 5-25% of family income of an average Indian.Aims & Objectives: To study the awareness of diabetes among the adolescents.Materials and Method: Community based cross-sectional study. We collected data from 600 adolescents of age group 16-18years. A questionnaire consisting of questions that were based on the knowledge, awareness and practices regarding the risk factors of Diabetes were prepared. Students from 4 pre-university colleges in Mangalore, Dakshina Kannada district, were selected as the study groupResults: 88.5% were aware of diabetes. According to 48.33% consumption of sweets only was a risk factor. 5.5% were aware that diabetes runs in families . 78.33 % were aware that diabetes can affect any age group and 73% knew about the increasing rate of diabetes in India. 72.16 % were sure that diabetes can be prevented and 25.5% said it was possible to completely cure .46% were under a misconception that a vaccine is present for diabetes and only 57.83%were aware of that diabetes can cause complications.
Keywords: awareness of diabetes; awareness of complications; prevention of diabetes